The Influence of The Work Environment on Organizational Citizenship Behavior Mediated by Job Satisfaction (Case Study of Employees of PT. Sketch Cipta Graha) - Yuni Putri Dewantara; Damelina Basauli Tambunan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The construction sector is a potential sector with many competitors. Competition in the construction sector is very competitive and companies with strong human resources are needed to win the competition. Organizational citizenship behavior plays a role in the company's success, because a successful company requires human resources who work beyond the set expectations, without expecting any imbalance. Organizational citizenship behavior is an act of extra HR role in a company, regardless of all the industries the company is involved in, including the construction service industry. In forming a strong OCB, several factors are needed to influence it, such as job satisfaction which can be influenced by the work environment. This study will examine the effect of the work environment on organizational citizenship behavior which is mediated by job satisfaction of employees at PT. Sketch of Cipta Graha, Surabaya. The sample in this study amounted to 33 people. This study uses the Structural Equation Model - Partial Least Square Method using SMARTPLS 3.0 software. Based on the results of data analysis, it can be interpreted that the work environment has a significant effect on job satisfaction, job satisfaction has a significant effect on the behavior of organizational members, the work environment has a significant effect on the behavior of organizational members, and job satisfaction mediates the significant influence of the work environment on the behavior of organizational members.